Resilience to childhood physical abuse - Araneda, Marcela; Castillo, Ramón; Haz, Ana María; Cumsille, Francisco; Muñoz, Sergio; Bustos, Luis; Román, Francisca (Revista de Psicología, 2000)
The present article shows the results of a study that describes and models variables distinguishing adults with a history of violence during their childhood that currently abuse their own children, from those adults that, having the same history of violence, do not abuse children in the present (resilient to severe physical child abuse). Findings support what has been exposed in the literature with respect to those individuals resilient to physical child abuse in the following lines: (a) they present more stable mental levels and (b) less environmental stressors. However, from the authors’ point of view, it is still needed to carry out new studies in order to establish greater levels of security of the observed tendencies of those subjecresilient to physical child abuse, and establish a stronger methodological model.